Analysis of Program and Financial Management of Physics Learning in SMA Taman Madya IP Yogyakarta City - Harianto, Harianto (Innovative: Journal Of Social Science Research, 2025)
AbstractThis study aims to analyze program planning and financial management in physics learning at SMA Taman Madya IP in Yogyakarta City. This is a qualitative study using a phenomenological approach. The subjects of this study are the school principal, school treasurer, and physics teachers. The data collection techniques used are interviews, observations, and document studies. Data analysis uses Spradley's model, which consists of domains, taxonomy, components, and structure. The results of this study indicate that program development at SMA Taman Madya IP has been carried out well, taking into account the general needs of the school with its vision, mission, and objectives based on national education standards. Financial management is categorized as good, implemented in accordance with the programs and activities carried out. For needs related to physics learning, more attention is needed to ensure that the expected learning objectives are achieved. Of course, this can be achieved through collaboration between relevant stakeholders. School activity plans and budgets are made efficiently and effectively in accordance with the available budget. The implementation of accountability and transparency in financial management at SMA Taman Madya IP is carried out in a limited manner and is accountable to relevant stakeholders, namely the Tamansiswa Foundation and the government.Keywords: Program, Financial Management, Physics Learning